Political Reform In Indonesia After Soeharto - Crouch, Harold (ISEAS, 2010)
Three decades of authoritarian rule in Indonesia came to a sudden end in 1998. The collapse of the Soeharto regime was accompanied by massive economic decline, widespread rioting, communal conflict, and fears that the nation was approaching the brink of disintegration. Although the fall of Soeharto opened the way towards democratization, conditions were by no means propitious for political reform. This book asks how political reform could proceed despite such unpromising circumstances. It examines electoral and constitutional reform, the decentralization of a highly centralized regime, the gradual but incomplete withdrawal of the military from its deep political involvement, the launching of an anti-corruption campaign, and the achievement of peace in two provinces that had been devastated by communal violence and regional rebellion.